The Effectiveness of Contextual Video in Increasing Students’ English Listening Comprehension: A Quasi-Experimental Study of Seventh Years Students of SMPN 13 Poleang Utara - Jusmaniar Nonci; Karmila Karmila (Journal of Research and Multidisciplinary, 2021)
The main purposes of this research are to investigate the effectiveness of the contextual videos in increasing students’ listening comprehension and students' interest in this technique. This research used the quantitative method and applied Time Series Design to find out the answers to the root problems. The sampling technique used in this research is cluster random sampling and use test and questionnaire as instruments. The tests include pre-test and post-test and distributed four times. The researcher analyzed the data through descriptive analysis and inferential analysis by using SPSS version 24. The result shows that after giving treatment, there is an improvement of students’ post-test simultaneously from the first post-test to the fourth post-test. It is proved that the mean score of students' last test on posttest is 85.00 which is categorized as high. Furthermore, the researcher found that students' responses to the questionnaire were positive. Regarding the hypothesis test, it proves that the t-test (2.333) is greater than > t-table (1.729), it can be concluded that H1 is accepted. Therefore, it can be concluded that contextual video effective in improving students’ listening comprehension at SMP Negeri 13 Poleang Utara and students are interested in this technique.